Respuesta :

Answer:

  • translation right 1 and up 3
  • reflection over the y-axis
  • see the attachment for a graph

Step-by-step explanation:

You want the sequence of transformations occurring to form g(x) = f(-x-1) +3.

Translation

Translation of f(x) by h units right and k units up is accomplished by ...

  g(x) = f(x -h) +k

The translation of f(x) right 1 unit and up 3 units will result in ...

  g(x) = f(x -1) +3

Reflection

Reflection of f(x) over the y-axis is accomplished by changing the sign of x:

  g(x) = f(-x) . . . . reflection over y-axis

Application

The given g(x) can be obtained a couple of ways. One is ...

  • Translation right 1 and up 3 to get g(x) = f(x -1) +3
  • Reflection over the y-axis to get g(x) = f(-x-1) +3

Doing this reflects the initial right translation to a left translation.

The graph is attached. (The blue curve is g(x).)

__

Alternatively, the given g(x) can be obtained by ...

  • Reflection over the y-axis to get g(x) = f(-x)
  • Translation left 1 and up 3 to get g(x) = f(-(x+1)) +3 = f(-x-1) +3

Since the reflection is done first, the translation is not reflected, but is applied to the reflected function.

Ver imagen sqdancefan
ACCESS MORE